3rd Independent Steering Committee Meeting, 30 April 2018 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
In April 2018 the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) held its third virtual Independent Steering Committee meeting.